Kombucha Batang Pisang Kepok: Kadar Fenolik Total, Aktivitas Antibakteri, dan Pengaruh terhadap Viabilitas Lactobacillus gasseri - Nur Laela; Fitri Husniatin Nisa; Riki Purwosutanto; Nur Hayati; Ernanin Dyah Wijayanti (PHARMADEMICA : Jurnal Kefarmasian dan Gizi, 2023)
Kepok banana pseudo stem (Musa acuminate balbisiana Colla) contains several secondary metabolites which have potential as antioxidants and antibacterials. Fermentation is known to increase the levels of phenolic compounds and their bioactivity. This study aims to analyze the effect of kombucha fermentation of kepok banana pseudo stems on total phenolic content, antibacterial activity and its effect on the viability of Lactobacillus gasseri. Banana pseudo stems were fermented with kombucha culture for 12 days at room temperature, the total phenolic content was determined by the Folin-Ciocalteu method, the antibacterial activity was tested by the well diffusion method, while the viability of L. gasseri was determined by the Total Plate Count (TPC) method. The total phenolic content of kepok banana stems increased by 60.88% after being fermented with kombucha, but the kombucha of kepok banana pseudo stems did not show antibacterial activity against Escherichia coli and caused a decrease in the viability of L. gasseri. This study shows that kombucha fermentation is beneficial for increasing phenolic levels and has potential as an antibacterial, especially against Gram positive groups.